Vocational Expectations and Adjustment at School: What Does the Relationship Between These Factors Suggest in Initial Vocational Training? - Pileičikienė, Nora; Bakšenskienė, Ingrida; Kovalčikienė, Kristina; Mičiulienė, Rita (Pedagogika, 2025)
The high dropout rate among vocational school students prompts us to examine the issues surrounding vocational expectations and adaptation within vocational education and training (VET) institutions as a potential factor contributing to this trend. This study adds to existing research on students’ professional expectations and adjustment within educational institutions, providing insights into the vocational training landscape. What sets this study apart is the inclusion of empirical data from 29 vocational education and training institutions (N = 377), offering a comprehensive overview of the alignment between vocational expectations and school adaptation among students in primary VET. Utilising descriptive and parametric statistical methods, the results revealed a moderately strong positive correlation between professional expectations and adjustment in VET institutions. The hypothesis that older students (post-12th grade) hold higher professional expectations than their younger counterparts in primary VET was supported. This corresponds to their superior personal-emotional and institutional adaptation. In comparison, the data indicates that younger students in primary VET (post-10th grade) have lower vocational expectations and poorer school adaptation. However, the correlation between their professional expectations and school adjustment is stronger than that of older students.